Pre- and Post-Treatment MR Imaging and Single Photon Emission CT in Patients with Dural Arteriovenous Fistulas and Retrograde Leptomeningeal Venous Drainage - Kai, Yutaka; Hamada, Jun-ichiro; Morioka, Motohiro; Todaka, Tatemi; Mizuno, Takamasa; Ushio, Yukitaka (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Dural arteriovenous fistulas (DAVFs) with disturbed regional cerebral blood flow (rCBF) include retrograde leptomeningeal venous drainage (RLVD). We examined rCBF disturbances in patients with DAVFs by studying MR imaging and single photon emission CT (SPECT) changes before and after treatment.METHODS: In 22 patients with DAVFs and RLVD, we studied their symptoms, pre- and post-treatment MR imaging and SPECT findings, and treatment results. Patients were assigned to two groups: Type 1 included those with RLVD into more than one venous sinus, and type 2, those with RLVD into a single venous sinus.RESULTS: Eleven patients had type 1 RLVD. In these patients, preoperative T2-weighted MR images showed no hyperintense areas, and angiographic evidence showed flow into more than one venous sinus. The other 11 patients had type 2 RLVD. In these patients, preoperative SPECT demonstrated hypoperfused areas that coincided with hyperintense areas on T2-weighted MR images. After treatment, the hyperintense areas disappeared, and symptoms improved in seven of these patients (type 2a). Their preoperative SPECT studies demonstrated preservation of vasoreactivity after an acetazolamide challenge. In the other four patients (Type 2b), the hyperintense areas and symptoms persisted after treatment. Their preoperative SPECT studies revealed a marked disturbance of vasoreactivity.CONCLUSION: In patients with drainage into a single venous sinus, we consistently observed areas of hyperintensity on MR images. These results and findings of hypoperfusion on SPECT scans apparently reflect venous congestion, whereas unpreserved vasoreactivity after an acetazolamide challenge on SPECT scans reflects venous infarction. The preservation of vasoreactivity after the challenge appears to be a good prognostic indicator.